On-Chip Thermal Gradients Created by Radiative Cooling of Silicon Nitride Nanomechanical Resonators - Bouchard, Alexandre (Université d'Ottawa / University of Ottawa, 2023)
Small scale renewable energy harvesting is an attractive solution to the growing need for power in remote technological applications. For this purpose, localized thermal gradients on-chip—created via radiative cooling—could be exploited to produce microscale renewable heat engines running on environmental heat. This could allow self-powering in small scale portable applications, thus reducing the need for non-renewable sources of electricity and hazardous batteries. In this work, we demonstrate the creation of a local thermal gradient on-chip by radiative cooling of a 90 nm thick freestanding silicon nitride nanomechanical resonator integrated on a silicon substrate at ambient temperature. The reduction in temperature of the thin film is inferred by tracking its mechanical resonance frequency, under high vacuum, using an optical fiber interferometer. Experiments were conducted on 15 different days during fall and summer months, resulting in successful radiative cooling in each case. Maximum temperature drops of 9.3 K and 7.1 K are demonstrated during the day and night, respectively, in close correspondence with our heat transfer model. Future improvements to the experimental setup could enhance the temperature reduction to 48 K for the same membrane, while emissivity engineering potentially yields a maximum theoretical cooling of 67 K with an ideal emitter. This thesis first elaborates a literature review on the field of radiative cooling, along with a theoretical review of relevant thermal radiation concepts. Then, a heat transfer model of the radiative cooling experiment is detailed, followed by the experimental method, apparatus, and procedures. Finally, the experimental and theoretical results are presented, along with future work and concluding remarks.
Keywords: Radiative Cooling; Nanomechanical Resonator; Silicon Nitride; Thermal Gradient